Cochlospermum planchonii Hook.f. ex Planch. and Cochlospermum tinctorium Perrier ex A. Rich.: extent of knowledge and prospects for sustainable use in West Africa - FAVI, Gnimanssou Abraham; DASSOU, Gbèwonmèdéa Hospice; ADOMOU, Aristide (My University, 2021)
Cochlospermum planchonii Hook.f. ex Planch. and Cochlospermum tinctorium Perrier ex A. Rich. are two wild edible plant species (WEPs), widely used in the West African Sudanian zone. Their parts are used as food additive, fodder, medical-magic and ethnoveterinary purposes, dye and arts. Unfortunately, the overexploitation of their rootstocks constitutes a great threat. While, an increasing number of studies reported on their uses, socio-economic importance, biological properties, and the anthropogenic pressure, knowledge on their reproductive biology, threats, domestication, and conservation status are still lacking. It therefore becomes crucial to systematically review literature on the current knowledge to identify research gaps and future research. Hence, this review aimed to critically synthetize knowledge, and gaps therein, to highlight future research for sustainable use and conservation of both species. To this end, publications were searched online in Web of Science, PubMed, Google Scholar, Science Direct, Springer Online and Research Gate, using following keywords: ‘‘taxonomy’’, ‘‘distribution’’, ‘‘ecology’’, ‘‘botanical description’’, ‘‘structural characteristics’’, ‘‘vernacular names’’, ‘‘uses’’, ‘‘plant parts used’’, ‘‘phytochemical’’ and ‘‘pharmacological properties’’, ‘‘economy’’, ‘‘propagation’’, ‘‘pollination’’, ‘‘reproduction’’, ‘‘threats’’, ‘‘conservation’’ and ‘‘domestication’’ in combination with ‘‘C. planchonii’’ or ‘‘C. tinctorium’’, ‘‘False-cotton’’. Out of 423 publications initially recorded, 165 were retained, of which 153 conducted in West Africa; the remaining 12 tackled botanical and taxonomical issues. Most of the publications addressed ethnobotany, chemical and pharmacological properties. Information obtained was compiled, critically analyzed, and discussed; knowledge gaps were keyed out and potential future research was highlited. The review confirmed the over-exploitation of both species mainly for human livelihoods. Both species were valuable sources of compounds and showed various pharmacological activities. A risk of genetic erosion was reported due overharvesting of their rootstocks whose powder was highly marketable. Future studies on their reproductive biology could enable their cultivation in order to reduce anthropogenic pressure and promote their sustainable use and conservation.
Keywords: Cochlospermum; Wild edible plants; Conservation ecology; Sustainable management; West Africa